Manfaat Dan Tantangan Yang Dihadapi Pada Penerapan Sistem Informasi Manajemen Dalam Pengambilan Keputusan Oleh Organisasi - Meisyah Ferianti Fadillah1; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The implementation of a management information system (SIM) is an important need for organizations to support the decision-making process. This research aims to identify the benefits obtained from implementing SIM as well as the challenges faced by organizations in the implementation process. This study uses a qualitative descriptive method with data collection through literature study. The research results show that SIM helps increase efficiency, data accuracy and speed of decision making, but also presents challenges in the form of user resistance, high cost requirements and dependence on technology. It is hoped that this study can be a reference for organizations that will or are currently implementing SIM to understand aspects of the benefits and challenges that may be faced in the implementation process.